2017
DOI: 10.1177/0363546517698675
|View full text |Cite
|
Sign up to set email alerts
|

Activity Level and Function 2 Years After Anterior Talofibular Ligament Repair: A Comparison Between Arthroscopic Repair and Open Repair Procedures

Abstract: When compared with open lateral ankle repair, arthroscopic repair of lateral ankle ligament when feasible produced similarly favorable outcomes. Arthroscopic ATFL repair, as a minimally invasive technique, provided favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 27 publications
(40 reference statements)
5
97
0
Order By: Relevance
“…By comparing the data of 37 patients undergoing open Broström repair surgery and 23 patients undergoing arthroscopic Broström repair surgery, Li et al . found that there was no significant statistical difference in AOFAS, KAFS, and Tegner score between the two groups after a 2‐year follow‐up. It is believed that arthroscopic surgery can achieve the same effect as open surgery.…”
Section: Introductionmentioning
confidence: 95%
“…By comparing the data of 37 patients undergoing open Broström repair surgery and 23 patients undergoing arthroscopic Broström repair surgery, Li et al . found that there was no significant statistical difference in AOFAS, KAFS, and Tegner score between the two groups after a 2‐year follow‐up. It is believed that arthroscopic surgery can achieve the same effect as open surgery.…”
Section: Introductionmentioning
confidence: 95%
“…Although the open modified Brostrom-Gould procedure is currently the gold standard for chronic lateral ankle instability, the arthroscopic repair of ATFL is be- [19], which also suggested comparable therapeutic efficacy at 3-year follow-up. We noticed that the patients in Yeo, Li, and Rigby' studies [15,17,18] involved several different accompanying intra-articular pathologies such as synovitis, anterior tibial spur, loose body, and OLTs. Matsui [16] and Zeng [19], however, enrolled only the patients without intra-articular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the open surgery, the arthroscopic technique has a smaller skin incision and less subcutaneous dissection, which may consequently shorten the surgical time. Through the standard portal in the ankle arthroscopy, the blood vessels around the ATFL can also be well protected in order to facilitate the vascularization of the repaired ATFL [15]. Meanwhile, as a less invasive technique, the bleeding and postoperative adhesion of the arthroscopic technique in the ankle joint was lower than that of the open surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations